The Origins and Development of á¹¢Å«fÄ« Orders (Tarekat) in Southeast Asia - Bruinessen, Martin van (Studia Islamika, 1994)
Any Theory of the Islamization of the Malay Archipelago will have to at least explain why the process began when it did, instead of some centuries earlier or later. Foreign Muslims has probably been resident in the trading ports of Sumatra and Java for many centuries, but it is only towards the end of the 13th century that the find traces of apparently indigenous Muslims. The first evidence is from the north coast Sumatra, where a few tini muslim kingdoms, or rather harbour states, arose; Perlak and the twin kingdoms of Samudra and Pasai. During the 14th and 15th centuries, Islam gradually spread across the coasts of Sumatra and the Malay peninsula, to the northern coast of Java and to the spice island in the east.DOI:Â 10.15408/sdi.v1i1.864